Computational fluid dynamics (CFD) simulation of level control process - Norhidayah Mohamad (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
This research presents the simulation fluid flow of model WLF922 Level Flow Process Control Training System that been used in Bioprocess Engineering Laboratory (UniMAP). In three dimensional geometry models of level process control was constructed by using Design Modeler ANSYS Fluent 15.0. Next the grid dependency study was performed by difference size of meshing been numerically simulated by using the Computational Fluid Dynamic (CFD) ANSYS Fluent 15.0. The boundary condition was applied to simulate based on the experimental parameters. The parameter that had been used varies with mass flow rate at 0.303 kg/s, 0.314 kg/s, 0.325 kg/s, 0.333 kg/s and 0.339 kg/s of water. The result showed that, medium mesh was selected for simulation because less than 30% percentage error and minimum time consuming to convergence. So it can save the time to simulate the model. The CFD model is validated by comparing the actual experimental result with the simulation result for control process.